Mobility and Hip Function Among Geriatric Patients With Displaced Neck of Femur Fractures Treated With Arthroplasty - Jade Pei Yuik, Ho; Amy Yoke Foong, Wong; Ong, Lik Han; Ankimtay, Rutel; Sabaruddin, Abdullah; Mohd Shahrul Azuan, Jaafar; Bong, Chun Haw; Tan, Kean Tee; Reuben Prashant, Rao; Faris, Kamaruddin (SAGE Publications Inc., 2023)
Abstract Background: Neck of femur fractures result in impaired function for older people. Despite surgery, many patients experience a decrease in functional level and poorer health status after the injury. The objectives of this study were (1) to determine the short-term mobility and hip function of geriatric patients who underwent hip replacement surgery for a displaced neck of femur fracture in our local population and (2) to identify factors which affect the functional outcome of these patients.